2000
DOI: 10.1111/j.1572-0241.2000.02186.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors predictive of response to cyclosporin treatment for severe, steroid-resistant ulcerative colitis

Abstract: Bands on admission are predictive of response to CSA and ultimately, the requirement for surgery in steroid-resistant UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(29 citation statements)
references
References 28 publications
0
24
0
2
Order By: Relevance
“…Additional randomized controlled trials showed similar effi cacy with an intravenous CSA dose of 2 mg / kg per day (275) , and CSA 2 mg / kg per day was as eff ective as hydrocortisone intravenously ( 276 ). Predictive factors for failure to respond to CSA include persistent fevers, tachycardia, elevated C-reactive protein, hypoalbuminemia, and deep colonic ulcerations ( 277,278 ).…”
Section: The Patient With Severe Colitis Refractory To Maximal Oral Tmentioning
confidence: 99%
“…Additional randomized controlled trials showed similar effi cacy with an intravenous CSA dose of 2 mg / kg per day (275) , and CSA 2 mg / kg per day was as eff ective as hydrocortisone intravenously ( 276 ). Predictive factors for failure to respond to CSA include persistent fevers, tachycardia, elevated C-reactive protein, hypoalbuminemia, and deep colonic ulcerations ( 277,278 ).…”
Section: The Patient With Severe Colitis Refractory To Maximal Oral Tmentioning
confidence: 99%
“…Among patients with severe UC who are unresponsive to conventional medical therapy 73% can avoid colectomy if administered with cyclosporin and after 5-6 months after the maintenance treatment, the response rate is 60% (17,18). These findings suggest that cyclosporin together with anticoagulant therapy could be an effective therapeutic approach to treating steroid resistant UC with complicating sinus thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other "risk scores" have been developed including those incorporating other blood-related parameters including low albumin and "bandemia" that have also been shown to be associated with poor outcomes in severe UC ( 40,41 ). Studies have established that fecal markers such as an elevated fecal calprotectin have been associated with higher risk of relapse in both UC and CD, as well as with outcomes in acute severe UC ( Table 1 ) ( 42 ).…”
Section: Fecal Calprotectin and Fecal Lactoferrinmentioning
confidence: 99%